Extreme hatred: revisiting the hate crime and terrorism relationship to determine whether they are “close cousins” or “distant relatives” - Mills, Colleen E. (Crime & delinquency, 2017)
Existing literature demonstrates disagreement over the relationship between hate crime and terrorism with some calling them “close cousins,” whereas others declare them “distant relatives.” We extend previous research by capturing a middle ground between hate crime and terrorism: extremist hate crime. We conduct negative binomial regressions to examine hate crime by non-extremists, fatal hate crime by far-rightists, and terrorism in U.S. counties (1992-2012). Results show that counties experiencing increases in general hate crime, far-right hate crime, and non-right-wing terrorism see associated increases in far-right hate crime, far-right terrorism, and far-right hate crime, respectively. We conclude that hate crime and terrorism may be more akin to close cousins than distant relatives